Accelerating Methane Reductions in Rice Production Systems Through Market-Based Mechanisms: Insight from Farmer Surveys and Choice Experiments in Vietnam - Villanueva, Donald B.; Labios, Jade Ruth; Pajadan, Karen M.; Revicoy, Riela Rose R.; De Castro, Allenie M.; Malana, Xyla Mae L.; Gonzalez, Tobiah Rey P.; Pascual, Franz Josef E.; Nghia, Tran Dai; Hai, Le Trong; Mirzabaev, Alisher (International Rice Research Institute, 2025)
Vietnam is one of the world’s leading rice producers and exporters. Its rice paddies also contribute significantly to methane emissions. This study gathered data from 597 rice farmers in five provinces – Thai Binh in Red River Delta, Nghe An in the North Central Coast, and An Giang, Kien Giang, and Soc Trang in the Mekong Delta – to understand their current practices, awareness about climate-smart agriculture (CSA), and willingness to adopt low-emission CSA practices. The findings aim to guide policies and investments that promote CSA, helping lower methane emissions while increasing farm productivity and improving livelihoods.